2003
DOI: 10.1017/s0305000903005622
|View full text |Cite
|
Sign up to set email alerts
|

A connectionist account of Spanish determiner production

Abstract: Evidence from experimental studies of Spanish children's production of determiners reveals that they pay more attention to phonological cues present in nouns than to natural semantics when assigning gender to determiners (Pérez-Pereira, 1991). This experimental work also demonstrated that Spanish children are more likely to produce the correct determiner when given a noun with phonological cues which suggest it is masculine, and more likely to assign masculine gender to nouns with ambiguous cues. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…They concluded that the acquisition of a certain number of lexemes, in other words a critical mass, was needed to start the process of creating abstract morphological patterns. Moreover, there would be no need to postulate a specific mechanism underlying grammar acquisition, contrary to the criteria proposed by other researchers (Marcus et al, 1992), and as other connectionist models have highlighted (Elman, 1999;Plunkett & Marchman, 1993;Smith, Nix, Davey, López-Ornat, & Messer, 2003).…”
Section: Direction Of the Relationship Between Lexical And Grammaticamentioning
confidence: 82%
“…They concluded that the acquisition of a certain number of lexemes, in other words a critical mass, was needed to start the process of creating abstract morphological patterns. Moreover, there would be no need to postulate a specific mechanism underlying grammar acquisition, contrary to the criteria proposed by other researchers (Marcus et al, 1992), and as other connectionist models have highlighted (Elman, 1999;Plunkett & Marchman, 1993;Smith, Nix, Davey, López-Ornat, & Messer, 2003).…”
Section: Direction Of the Relationship Between Lexical And Grammaticamentioning
confidence: 82%
“…The preference for masculine, however, likely has nothing to do with code-mixing tendencies per se, but may rather simply follow from patterns and preferences that are internal to Spanish. In a connectionist analysis of a longitudinal database of parental production, Smith et al (2003) noted that "while regular feminine nouns were slightly more frequent than regular masculine nouns, irregular masculine nouns outnumbered irregular feminine nouns by roughly 2 to 1" (p. 306). Based on this input, which preserved type and token frequencies, a computer-generated model produced a similar bias toward masculine gender assignment to novel words, suggesting that the frequency distribution has a direct role in gender assignment.…”
Section: Gendermentioning
confidence: 99%
“…By 3 years, 0 months (3;0) of age, children demonstrate correct use of gender and number agreement, with minimal errors (cf. Barreña, 1997;Clark, 1985;Hernández-Pina, 1984;Idiazabal, 1995;Smith, Nix, Davey, López Ornat, & Messer, 2003). Early acquisition of the determiner system in Spanish has been ascribed to the relatively uniform and rich determiner-noun agreement paradigm (Baauw, 2002).…”
Section: Spanish Npsmentioning
confidence: 99%